Open innovation deficiency: Evidence on project abandonment and delay - Kristof van Criekingen; Mark Freel; Dirk Czarnitzki (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
The concept of Open Innovation (OI) has breathed new life into both empirical research and industry practice concerned with distributed and collaborative modes of innovating. Certainly, the volume of OI research and its impact on practice has been remarkable. However, equally remarkable is the lack of balance. With few exceptions, the stories of OI are positive stories. A unbalanced focus on successes leads to open innovation imperatives and the conclusion that, for most firms, openness is good, and more openness is better. In this paper, we nuance this perception by empirically investigating the relationships between innovation openness and its effects on project abandonment and delays. Using survey data from Belgium, we find that open innovation strongly associates with an increased risk of both project abandonment and project delays.
Keywords: O31; 330; Open innovation; collaboration; project abandonment